Renal function and hyperfiltration capacity in lead smelter workers with high bone lead. Issue 8 (August 1994) - Roels, H; Lauwerys, R; Konings, J; Buchet, J P; Bernard, A; Green, S; Bradley, D; Morgan, W; Chettle, D
Abstract : OBJECTIVE--The study was undertaken to assess whether the changes in urinary excretion of eicosanoids (a decrease of 6-keto-PGF1 alpha and PGF2 and an increase of thromboxane) previously found in lead (Pb) exposed workers may decrease the renal haemodynamic response to an acute oral protein load. METHODS--The renal haemodynamic response was estimated by determining the capacity of the kidney to increase the glomerular filtration rate (in terms of creatinine clearance) after an acute consumption of cooked red meat (400 g). A cross sectional study was carried out in 76 male Pb workers (age range 30 to 60 years) and 68 controls matched for age, sex, socioeconomic state, general environment (residence), and workshift characteristics. RESULTS--The Pb workers had been exposed to lead on average for 18 (range 6-36) years and showed a threefold higher body burden of Pb than the controls as estimated by in vivo measurements of tibial Pb concentration (Pb-T) (geometric mean 66 v 21 micrograms Pb/g bone mineral). The geometric mean concentrations of Pb in blood (Pb-B) and Pb in urine (Pb-U) were also significantly higher in the Pb group (Pb-B: 430 v 141 micrograms Pb/l; Pb-U: 40 v 7.5 micrograms Pb/g creatinine). These conditions of chronic exposure to Pb did not entail any significant changes in the concentration of blood borne and urinary markers of nephrotoxicity, such as urinary low and high molecular weight plasma derived proteins (beta 2-microglobulin, retinol binding protein, albumin, transferrin), urinary activities of N-acetyl-beta-D-glucosaminidase and kallikrein, and serum concentrations of creatinine, beta 2-microglobulin, urea, and uric acid. All participants also had normal baseline creatinine clearances (> 80 ml/min/1.73 m2) amounting on average to 115.5 in the controls v 121.3 ml/min/1.73 m2 in the Pb group. Both control and Pb exposed workers showed a significant increment in creatinine clearance (on average 15%) after oral protein load suggesting that the previously found changes in secretion of urinary eicosanoids apparently has no deleterious effect on renal haemodynamics in the examined Pb workers. CONCLUSIONS--The finding that both baseline and stimulated creatinine clearance rates were not only significantly higher in the Pb workers but also positively correlated with Pb-T, suggests that moderate exposure to Pb may be associated with a slight hyperfiltration state, which has been found to attenuate the age related decline in baseline creatinine clearance by a factor of two. Although the relevance of this effect for the worker's health is unknown, it can be concluded that adverse renal changes are unlikely to occur in most adult male Pb workers when their blood Pb concentration is regularly kept below 700 micrograms Pb/l. One should, however, be cautious in extra-polating this conclusion to the general population because of pre-employment screening of the Pb workers for the absence of renal risk factors.